The effectiveness of cooperative learning model type think-pair and share assisted by learning videos on the motivation and learning outcomes of christian religious education - Milton Thorman Pardosi (Jurnal Konseling dan Pendidikan, 2022)
Motivation in teaching and learning activities encourages students' enthusiasm and willingness to learn something and maintain perseverance in the process of learning activities, and can improve learning outcomes. Cooperative learning with think-pair-and-share type is an effective strategy to increase motivation and learning outcomes. This research aims to test the influence of cooperative learning approaches with learning videos on student motivation and learning outcomes in Christian religious education, deviating from previous learning. The method used is an pre-experimental approach with one group pre-post-testin which 50 students in grades 10, 11, and 12 of the Bandung Adventist Christian High School (Naripan) and Cimindi Bandung Adventist College were involved in this study. Non-probability sampling using the saturated sample method was used in this study. Researchers used a Likert scale 1-5 to determine the value in this experiment. The scale is (1) srrongly disagree, (2) disagree, (3) slightly agree, (4) agree, and (5) very agree. This research is analyzed quantitatively using SPSS 26 version. The results show that students' enthusiasm for learning and their performance on standardized tests increased when the Think Pair Share (TPS) cooperative learning paradigm was used. Students are better able to understand the material being taught when using the Think Pair Share (TPS) cooperative learning model.